The management of sporting innovation at Decathlon. Between rationality and chaos. - Richard, G.; Abdourazakou, Y. (The Engineering of sport 7, Volume 2, 2008)
The point under study is the first of such a nature. We investigated the management of innovation in the Company called Decathlon. In recent years, vertical Integration has rarely been so much developed as in the leading Company of sporting goods' distribution in France. Based on the group's "sporting universe" concept, it now challenges some bigger firms' on their main segment. We interviewed the head of innovation for Decathlon's brands in France and Europe. Since the 1990's, Decathlon's strategies have not taken a unique and rational way towards success. Sometimes unexpected, they do not fit the traditional and rational management model of this aspect of competition between firms. Finally, some non technological aspects of innovation play a key role in the group's success. Now a major force in the domain of sports equipment, the Company Decathlon represents today almost half the French market in the distribution of sporting articles. From bikes to rucksacks, from hiking boots to tennis rackets, this brand has acquired a great deal of savoir-faire in the conception, the realization and the production of its "universe" brand. By way of an example, Decathlon is the biggest producer of bikes (Btwin) in the whole of France, the number 1 in the country for rucksacks and the fourth largest producer in the world of sporting goods. The producer of sporting equipment has thus made the choice of a differentiation through innovation 2. The model of innovation used by the Company has allowed it to obtain a durable advantage in relation to other distribution brands such as Intersport and Go Sport. Its originality is based on a culture of innovation associated with certain values such as pleasure, accessibility and a "practical" character regarding the use of the products. How has the Company developed two of its leading products? The "2 second" tent and the wet suit "Inergy" illustrate the production logic of the "sporting" innovation at Decathlon. Based on a resources approach, the objective of this research project was to study the organizational capacities developed by the group in terms of "sporting" innovation.